Heberto H. Fernández Urdaneta. Dictionaries in Spanish and English from 1554 to 1740: Their Structure and Development. - J.C.M.D. du Plessis (Woordeboek van die Afrikaanse Taal-WAT, 2012)
Review of Dictionaries in Spanish and English from 1554 to 1740: Their Structure and Development.